2017
DOI: 10.21276/apjhs.2017.4.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Study of Preanalytical errors in hematology laboratory of a tertiary care hospital

Abstract: Laboratories play an important role in the diagnosis and management of the disease. Errors are part and parcel of human nature. Its human tendency to make errors. Automation in laboratories has reduced the number of errors but still few errors do occur. Present study was undertaken to evaluate different types & frequencies of pre-analytical errors in hematology laboratory of a tertiary care hospital. Methods: Present study is a prospective study. All the samples received in hematology laboratory of our hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This is the only study which included samples from Hematology, Biochemistry and Microbiology. Other studies conducted by Shashi Upreti et al, Shukla et al, Narang et al and Pavani B [4][5][6][7][8] No study showed pre-analytical errors of urine samples. Our study more or less correlates with the above studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the only study which included samples from Hematology, Biochemistry and Microbiology. Other studies conducted by Shashi Upreti et al, Shukla et al, Narang et al and Pavani B [4][5][6][7][8] No study showed pre-analytical errors of urine samples. Our study more or less correlates with the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Shukla et al, Narang et al and Sumera Naz et al showed the most common cause of pre-analytical error was clotted sample, whereas study conducted by Pavani B et al showed the most common cause of pre-analytical error was mismatch sample. [4][5][6][7][8] This is because the nursing staff didn't draw enough volume of blood and few samples were hemolysed on transportation.…”
Section: Discussionmentioning
confidence: 99%